Pembangunan Kompetensi Kemahiran Teknikal bagi Sektor Pengangkutan di Malaysia - ISMAIL, AFFERO; KASMAN, ZETI (MINDA MASAGI PRESS, 2020)
The Development of Technical Skill Competency in Malaysian Transportation Sector”. Promoting the use of green technology to protect the environment is a major challenge in today’s world. Human activity that affects the environment must be efficiently addressed to ensure that efforts to maintain the environment can be achieved. Referring to the above issues, individuals entering the industry must be equipped with sufficient skills and knowledge in relation to green skills. However, today’s scenario shows that individuals entering the industry world have no relevant qualifications. In the labor market, these individuals are considered to be lowskilled workers as they have no prior training. Therefore, specialized training should be provided for them to improve their skills. This study – adopt a qualitative approach by interviewing experts in Focus Group Discussion as well as analysis of the Duzhi Fuzzy Method to identify the consensus of experts – is conducted to develop competence of technical skills based on CUDBAS (Curriculum Development Based on Skill Structure). It is used in this research as it provides a clearer perspective on the level of knowledge, competence, and skills of employees in carrying out their duties, especially in the transportation sector in Malaysia. The biggest impact of this study is to produce highly skilled workers to increase organizational productivity towards a high-income nation.